(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Vaccination is a method of creating artificial immunity, which is a method of protecting the body from disease-causing infections by introducing antigens of pathogenic microorganisms into the body. After introducing the antigen of the microorganism into the body, special antibodies are produced against it. Vaccination is carried out for preventive and therapeutic purposes. The vaccine is more effective if it is prepared from live but weakened strains of pathogenic microorganisms (approximately 10-15%), while vaccines prepared from dead microorganisms require the body to develop immunity for a long time. In modern medicine, both types of vaccines are administered, especially inactivated (dead microorganisms) vaccines are often used in children under school age. (1).